تشخيص دور التجربة الجزائرية في توفير مختلف اليات الدعم المالي لتنمية تطور مسار المؤسسات الصغيرة والمتوسطة - بلهاشمي, جهيزة; بلحوت, عبد المجيد (جامعة الوادي - University of Eloued, 2018)
إن نمو المشاريع الاستثمارية من قبل المؤسسات الصغيرة والمتوسطة وتطورها وزيادة حجمها، وزيادة التنافس على إقامتها جعلت العديد من الدول وخاصة الجزائر تبحث عن البدائل التي تمكنها من مسايرة المنافسة وتطوير الاستثمار بما يتماشى وتطلعات الدولة، وإبراز مركزها بين الدول من خلال تطور استثماراتها. فقد أصبحت الجزائر تشجع وتحث وتبحث عن كل البدائل لإقامة المشاريع وذلك من خلال تشجيعها للمؤسسات وتقديمها الدعم المالي اللازم ،بالنظر الى الاصلاحات والبرامج التأهيلية المسطرة للرقي بهذا القطاع فالحكومة الجزائرية عملت على توفير مختلف الاليات التي تعمل على دعم استمرار نمو المؤسسات الصغيرة والمتوسطة من خلال مختلف الهيئات التابعة لها . The growth of investment projects by small and medium enterprises, their development and increasing their size, and increased competition for their establishment have made many countries, especially Algeria, looking for alternatives that enable them to keep pace with competition and develop investment in line with the aspirations of the state and to highlight its status among countries through the development of its investments. Algeria encourages and looking for all alternatives to establish projects by encouraging institutions and providing them with the necessary financial support. In view of the reforms and rehabilitation programs in place to promote this sector, the Algerian Government has provided various mechanisms that support the continued growth of SMEs through various bodies Affiliate.
Diagnosing the role of the algerian experience in providing various machanisms of finanncial support to the developement of the path of small and medium enterprises.
مقال
Keywords: اليات الدعم الحكومي ،المؤسسات الصغيرة والمتوسطة، المشاريع الاستثمارية .; Government support mechanisms, SMEs, investment projects.